Why students drop out of the Bachelor of Arts. Issue 5 (2nd September 2016) - Mestan, Kemran
ABSTRACT: Attrition, which courses in the humanities and social sciences particularly suffer from, is a major problem for universities and students. This paper investigates the reasons students give for prematurely discontinuing studying the Bachelor of Arts. This is a qualitative study that thematically analyses semi-structured interviews. The sample represented a cross-section of the population of students enrolled in the course. The reasons for attrition can be divided into course-related or personal reasons. Amongst course-related reasons, the most important relate to: career direction and purpose, subject range and peer bonding, as well as teaching quality. Personal issues that interfere with study relate to illness, finances and employment. Course-related and personal reasons also interact and reinforce each other, with students studying the humanities and social sciences more vulnerable to personal pressures due to course-related reasons. Student engagement with support services is also analysed, and conclusions drawn on how attrition can be addressed.